Public financial support to investments in rural areas: The case of the region of Thessaly in Greece - Simeon Karafolas (International Journal of Economic Sciences and Applied Research, 2013)
Greek governments have supported investments to rural areas financially either by covering part of the investment and/or offering advantages with respect to interest rate loans or tax advantages. This support had been tendered either by nationally financed programs, called Development Laws, or by other programs, mainly financed by the European Union. The financial support depended on the area where the investment took place, as well as the sector and the nature of the investment. Additionally, another program, the LEADER initiative, was developed. It was financed mainly by the European Union, in order to support investments in rural areas and promote the development and the structural adaptation of the less developed European regions. This paper examines public financial support for investments in rural areas in the case of the region of Thessaly, one of the 13 regions in Greece. Its aim is to point out the importance of investments in the sectors of tourism, industry and agriculture. The region of Thessaly presents obvious interest because of the development of these sectors at different levels, depending on local production characteristics. The time period is the 2000s, when important investments were undertaken in the region, supported financially by Development Laws and the LEADER initiative.
Keywords: G32; H54; R51; 330; Financial support; investments; rural areas; Thessaly; Greece